The forest behind the tree: phylogenetic exploration of a dominant Mycobacterium tuberculosis strain lineage from a high tuberculosis burden country - Oelemann, Maranibia Cardoso (2011)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Biologia Molecular Aplicada a Micobacterias. Rio de Janeiro, RJ, Brasil.